Recombinant Expression and Characterization of a Novel Thermo-Alkaline Lipase with Increased Solvent Stability from the Antarctic Thermophilic Bacterium Geobacillus Sp. id17 - Blamey-Alegria, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Lipases are enzymes that hydrolyze long-chain carboxylic esters, and in the presence of organic solvents, they catalyze organic synthesis reactions. However, the use of solvents in these processes often results in enzyme denaturation, leading to a reduction in enzymatic activity. Consequently, there is significant interest in identifying new lipases that are resistant to denaturing conditions, with extremozymes emerging as promising candidates for this purpose. Lip7, a lipase from Geobacillus sp. ID17, a thermophilic microorganism isolated from Deception Island, Antarctica, was recombinantly expressed in E. coli C41 (DE3) in functional soluble form. Its purification was achieved with 96% purity and 23% yield. Enzymatic characterization revealed Lip7 to be a thermo-alkaline enzyme, reaching a maximum rate of 3350 U mg−1 at 50 °C and pH 11.0, using p-nitrophenyl laurate substrate. Notably, its kinetics displayed a sigmoidal behavior, with a higher kinetic efficiency (kcat/Km) for substrates of 12-carbon atom chain. In terms of thermal stability, Lip7 demonstrates stability up to 60 °C at pH 8.0 and up to 50 °C at pH 11.0. Remarkably, it showed high stability in the presence of organic solvents, and under certain conditions even exhibited enzymatic activation, reaching up to 2.5-fold and 1.35-fold after incubation in 50% v/v ethanol and 70% v/v isopropanol, respectively. Lip7 represents one of the first lipases from the bacterial subfamily I.5 and genus Geobacillus with activity and stability at pH 11.0. Its compatibility with organic solvents makes it a compelling candidate for future research in biocatalysis and various biotechnological applications. © 2024 by the authors.